2020
DOI: 10.1155/2020/4760512
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tooth Loss with New-Onset Parkinson’s Disease: A Nationwide Population-Based Cohort Study

Abstract: Introduction. Tooth loss is associated with poor oral hygiene. During insufficient oral sanitation, focal infection and inflammation can occur and these reactions may induce systemic inflammation. Systemic inflammatory reaction may be related to the degeneration of dopamine neurons in the substantia nigra. We hypothesized that tooth loss is related to increased risk of new-onset Parkinson’s disease. Methods. Between 2003 and 2006, we included 153,165 participants from the national health insurance system-healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…The number of Parkinson’s patients visiting dental clinics to be treated with complete dentures is increasing 11 . Previous report showed that the number of tooth loss was positively correlated with a higher risk of development of newly onset Parkinson's disease in a longitudinal study setting 12 . Increased susceptibility to periodontitis in Parkinson’s disease is reported in the individuals with Parkinson’s disease 11 .…”
Section: Introductionmentioning
confidence: 86%
“…The number of Parkinson’s patients visiting dental clinics to be treated with complete dentures is increasing 11 . Previous report showed that the number of tooth loss was positively correlated with a higher risk of development of newly onset Parkinson's disease in a longitudinal study setting 12 . Increased susceptibility to periodontitis in Parkinson’s disease is reported in the individuals with Parkinson’s disease 11 .…”
Section: Introductionmentioning
confidence: 86%
“…Periodontitis is defined as an inflammatory disease of the supporting tissues of teeth caused by specific microorganisms or groups of specific microorganisms, resulting in progressive destruction of the periodontal ligament and alveolar bone with periodontal pocket formation, gingival recession, or both [ 5 ]. Emerging evidence suggests that poor oral health and periodontitis can influence the initiation and/or progression of various diseases such as cancer, cardiovascular disease, metabolic disease, and degenerative diseases [ 6 , 7 , 8 , 9 ]. On the other hand, behaviors improving oral health may reduce the risk of medical illnesses [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent population-based cohort study from the same group noted that dental scaling over 5 consecutive years has a protective effect against development and progression of PD in patients with and without periodontal disease (Chen et al 2018). Another group found a positive correlation between an increase in tooth loss and the development of new-onset PD in a longitudinal study (Woo et al 2020). Studies reported by these groups showed for the first time that oral dysbiosis and poor oral health might predispose patients to developing PD.…”
Section: Periodontitis and Neurodegenerative Diseasesmentioning
confidence: 99%